Generasi Z dan Kecintaan Mereka Pada Merek Kosmetik Halal - Putri, Erlina Meidiana; Qurniawati, Rina Sari (Peneliti.net, 2023)
The demand for halal products is a new phenomenon in the global cosmetic industry so that halal branding appears. With existing policies and regulations, cosmetic industry players, especially skincare, must comply with the rules and regulations that apply in Indonesia. In this study, the issue raised is whether the determinants of brand love, namely religious belief and brand experience, have an effect on e-WOM generation Z consumers who use halal skin care. This study aims to review and explain the role of brand love in mediating the influence of religious beliefs and experiences. brand against e-WOM. The number of samples in this study were 157 respondents who are generation Z, users of halal skincare using a purposive sampling method. The analysis technique used was Path Analysis using SmartPLS version 3. The results showed that religious beliefs and brand experiences had a positive and significant effect on brand love. Brand love influences e-WOM and is able to mediate the relationship between brand experience and e-WOM. Therefore, it is important for halal skincare entrepreneurs to actively carry out social media promotions so that love for their brand increases and is able to attract new buyers.